2017
DOI: 10.1186/s40824-017-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of covering materials composed of biodegradable polymers enriched with flax fibers

Abstract: BackgroundThe objective of this study was to investigate the in vivo effect of bioactive composites with poly(lactic acid) (PLA) or polycaprolactone (PCL) as the matrix, reinforced with bioplastic flax fibers, on the surrounding muscle tissue.MethodsMaterials of pure PLA and PCL and their composites with flax fibers from genetically modified plants producing poly-3-hydroxybutyrate (PLA-transgen, PCL-transgen) and unmodified plants (PLA-wt, PCL-wt) were placed subcutaneous on the M. latissimus dorsi for four we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Fibrous capsule formation reflects the final step of healing of a wound generated by implantation, and the capsule thickness indicates the biocompatibility of the material in the body. It is postulated that a material with better biocompatibility produces a thinner capsule [39,40]. In our case, microscopic observation revealed that thin capsules with thicknesses varying from 27 to 46 μm had formed around all the implanted specimens for both PLA and PCL-based materials (Figure 9a).…”
Section: Resultsmentioning
confidence: 51%
“…Fibrous capsule formation reflects the final step of healing of a wound generated by implantation, and the capsule thickness indicates the biocompatibility of the material in the body. It is postulated that a material with better biocompatibility produces a thinner capsule [39,40]. In our case, microscopic observation revealed that thin capsules with thicknesses varying from 27 to 46 μm had formed around all the implanted specimens for both PLA and PCL-based materials (Figure 9a).…”
Section: Resultsmentioning
confidence: 51%
“…This is supported by a previous study including an in vivo analysis of PCL matrix placed subcutaneously above the LD muscle in a rat model, showing favorable biocompatibility at the histological level. 12 Third, PCL is expected to be osteoinductive through further utilization of biological additives such as BMP2 or bone marrow-derived mesenchymal stem cells. 13 In-vivo experiments showed that BMP2-adsorbed PCL scaffold showed larger regenerated bone volume regeneration, 14 and there is a case report of successful calvarial reconstruction with stem cell-impregnated PCL Osteomesh in combination with a local flap.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a previous study including an in vivo analysis of PCL matrix placed subcutaneously above the LD muscle in a rat model, showing favorable biocompatibility at the histological level. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Ceramics are known for their excellent biocompatibility, high corrosion resistance and better compression strength. [283][284][285][286] Ceramic structures resemble natural bone, making them a favorable choice as biomaterials. Today, bioresorbable ceramics, such as calcium phosphate, tricalcium phosphate, tetra-calcium phosphate, alumina and ferric oxide, are already being studied.…”
Section: Bioresorbable Ceramicsmentioning
confidence: 99%